Should The United States Designate Specialist Patent Trial Judges? An Empirical Analysis of H.R. 628 In Light of the English Experience and the Work of Professor Moore - Gitter, Donna M. (Science and Technology Law Review, 2009)
The United States Court of Appeals for the Federal Circuit currently reverses from one-third to nearly one-half of all U.S. district court patent claim construction decisions. Because claim construction often determines the outcome of patent litigation, the high appellate claim construction reversal rate contributes to significant uncertainty among inventors and investors. Congress is currently considering legislation, H.R. 628, which will designate specialist district court patent judges to reduce this unacceptably high reversal rate. This Article concludes that designation of specialist patent trial judges among the federal district court judiciary is likely to reduce the high appellate claim construction reversal rate, based upon an empirical analysis of the appellate claim construction reversal rate in England, which has specialized patent tribunals. Part I of the Article examines proposed U.S. legislation that would designate specialized patent trial judges. Part II analyzes the patent claim construction process in the United States, enumerating the challenges faced by generalist U.S. district court judges charged with deciding highly complex patent litigation actions. Part III then examines the English patent claim construction process, drawing numerous parallels between patent litigation in the United States and England that render the English system a valid comparator when considering the respective appellate claim construction reversal rates in the two jurisdictions. Part IV presents empirical results that strongly support the notion that designation of specialist patent trial judges in the United States could indeed decrease the appellate claim construction reversal rate, thereby affording certainty to patent litigants and investors. Part V then explains why the approach proposed in H.R. 628 is superior to the current English system of specialized patent trial courts.